2018
DOI: 10.1561/107.00000052
|View full text |Cite
|
Sign up to set email alerts
|

Occasion Matching of Indulgences

Abstract: While much is known about how consumers choose products for purchase, less is known about how they determine the timing of their consumption. For certain products, consumers put substantial effort into this timing decision by trying to match consumption to a special occasion. Occasion matching happens most often for items that are considered indulgences or otherwise labeled as special-typically outside the consumer's regular spending, received as a gift, and/or valued above market value. Consumers who engage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(60 reference statements)
0
3
1
Order By: Relevance
“…Past literature on scarcity might on the surface appear to predict the opposite of our results; that is, people might be less likely to spend their resources from a used account than from an unused account (Soster et al, 2014; Zhu & Ratner, 2015) or hold on to the resources that appear limited for a longer period of time (Shu & Sharif, 2018). For example, Soster et al (2014) found people were less satisfied when they spent from an account that had absolutely less (vs. absolutely more) in the account.…”
Section: Discussioncontrasting
confidence: 90%
“…Past literature on scarcity might on the surface appear to predict the opposite of our results; that is, people might be less likely to spend their resources from a used account than from an unused account (Soster et al, 2014; Zhu & Ratner, 2015) or hold on to the resources that appear limited for a longer period of time (Shu & Sharif, 2018). For example, Soster et al (2014) found people were less satisfied when they spent from an account that had absolutely less (vs. absolutely more) in the account.…”
Section: Discussioncontrasting
confidence: 90%
“…If efficiency becomes an end itself in completing daily tasks, it is likely to undermine experiences in general and lead to the postponement of personal experiences due to waiting for the perfect “occasion matching” (Shu & Gneezy, 2010; Shu & Sharif, 2018). However, efficiency can also be a means to an end (a) when the delegation of task execution to nonconscious processes allows greater conscious attention to be focused on the experience of the action and (b) when everyday tasks are done quickly and efficiently so that one would have opportunities to do things h/she really enjoys doing.…”
Section: Repeating With Varietymentioning
confidence: 99%
“…First, as reviewed, one’s final consumption opportunity for a while likely feels like an event that people may prefer to match appropriately (akin to “occasion matching”; Shu & Sharif, 2018)—and people might view something that is meaningful as an especially appropriate match for that moment (vs. something that offers purely exciting stimulation, for example). Broadly speaking, personal meaning is regarded as among the most elevated attributes with which to imbue an experience (King et al, 2006; King & Napa, 1998).…”
Section: Novelty Versus Familiaritymentioning
confidence: 99%
“…These diverse examples illustrate that, generally speaking, ending contexts impel people to choose whichever hedonic activities they think will help them "make the most" of the moment. Knowing that one is about to have one's last chance to enjoy an activity for some time may feel like an event that people will thus want to honor and match accordingly (Shu & Sharif, 2018). Returning to our research question, we ask: What kind of experience-a novel option or familiar option-do people pursue to make the most of the moment?…”
Section: The Psychology Of Endingsmentioning
confidence: 99%